ANALISIS ARUS KAS, DISAGREGAT LABA DALAM MEMPREDIKSI ARUS KAS MASA DEPAN - Synthia Madyakusumawati (Jurnal Akuntansi Bisnis, 2018)
The purpose of this research is to analyze the impact of cash flow, earnings and disagregat earnings in predicting future cash flow. Hypothesis testing is carried out by using regression model using financial statement data from BEI 2012-2016. The result of this study indicate that the current cash flow have the most powerful tools in predicting future cash flow Keyword : cash flow, aggreagate earnings, earnings, future cash flow